Ultrawideband antenna arrays on Сlavin radiators - Fomin, P.G.; Dumin, O.M; Plakhtii, V.A.; Nesterenko, M.V. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2023)
Background. Slot antennas have become widespread due to their good electrodynamic parameters, ease of excitation, and convenient geometry for integration into various devices. As a rule, such antennas are narrowband due to the resonant phenomena that occur in them. However, the use of a complex slot geometry makes it possible to significantly extend the operating frequency range of such a radiator by changing the characteristic impedance along the slot arm, which generates partial reflections of waves at different frequencies in different places of the metal screen cut. The successful law of change of the slot shape from the coordinate makes it possible to provide relatively uniform radiation characteristics of such antenna in the frequency range of several octaves The combination of a slot as a magnetic radiator with a vibrator as an electric radiator dual to the slot can create an opportunity for mutual compensation of the deficiency of one of these antennas at certain frequencies, if the other antenna is effective at these frequencies. This design is called an ultra-wideband Clevin antenna. However, there is an urgent need to increase the radiated energy of the electromagnetic wave and better concentrate its energy in a given direction. One of the solutions to these problems is to create an antenna array based on the combined single radiators described above, which is the subject of this paper. Objectives. To develop antenna array designs based on single combined Klevin radiators, taking into account their interaction and the possibility of simultaneous use of elements of one radiator for another radiator in order to create more compact designs. The latter will not only reduce the size, save resources, but also reduce side radiation. It is also necessary to calculate the radiation characteristics of the resulting arrays and analyze their directivity parameters. Additionally, it is necessary to optimize a single radiating element in order to improve its characteristics compared to our previous work. Materials and methods. The problem of radiation of the obtained antenna array structures is solved by numerical methods in time domain. This approach makes it possible to accurately take into account all the design features of the constructed arrays. Results. The voltage standing wave ratio of a single radiator in a wide frequency range is improved by finding more optimal slot dimensions and its shape. Three antenna array configurations based on ultra-wideband analogs of the Clavin radiator were designed and calculated. The time dependences of the amplitudes of the radiated waves in the far-field in the E- and H-planes were obtained by direct numerical calculation. Conclusion. The possibility of using an ultra-wideband analog of the Clavin emitter for the construction of antenna arrays, including increased compactness due to the double use of one ultra-wideband dipole by two adjacent slots, is shown. The energy gain in the radiated field due to the construction of the antenna array is illustrated. The angular dependence of the main radiation characteristics shows the ability to effectively direct ultra-wideband waves without deteriorating their time shape. A stronger change in the shape of the radiated pulse from the angle of the considered antenna arrays can improve the parameters of the pulse positioning system.